There must be an angel? Local financial markets, business angels and the financing of innovative start-ups. Issue 5 (4th May 2019) - Grilli, Luca
ABSTRACT: This study addresses the question of whether business angels can fill the gap left by venture capitalists and banks in the financing of innovative start-ups in regions where there is a relatively thin financial supply of bank loans and venture capital investments. The empirical analysis, based on approximately 2000 Italian ventures, highlights the fact that innovative start-ups located in weak local financial ecosystems show a relatively low probability of getting business angel financing. In these areas, angel investing is unlikely to represent a viable and effective informal solution to alleviate regional financing gaps towards innovative start-ups left by more institutionalized financial intermediaries.